Nieszczęśliwe wypadki w Gdańsku na łamach gazety „Danziger Monathliche Sammlung” (1773–1792) - Kubus, Radosław (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
This article analyses reports of accidents in the manuscript newspaper Danziger Monathliche Sammlung that appeared in Gdansk between 1773 and 1792. Among the many such pieces, information on drowning and injuries caused by falls from heights was predominant. There were almost no records offirevictims onaccount of thecity’s well-functioning firefighting system. Accident victims were mostly unskilled workers in the manufacturing industry and seamen. The type of care and the form and place of their funerals depended not so much upon the kind of accident as on the victim’s social status.
p. 5-37 : illustration
Keywords: forensic medicine; accidents; public health; early modern society; Gdansk (Poland; region) - 18th c.; attitude towards health; violent death